2013
DOI: 10.1055/s-0033-1340042
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis of Hydrazine Derivatives of 5H-Pyrrolo[3,4-b]pyrazine and 1H-Pyrrolo[3,4-b]quinoxaline

Abstract: A convenient and efficient route for the chemoselective synthesis of carbohydrazide, arenesulfonylhydrazide, and thiosemicarbazone derivatives of 5H-pyrrolo[3,4-b]pyrazine and 1H-pyrrolo [3,4-b]quinoxaline from the corresponding dinitriles and substituted hydrazines was elaborated. The synthesis of starting pyrazine-2,3-dicarbonitrile was sufficiently improved by using concentrated HCl as a catalyst. pyrazine and 1H-Pyrrolo[3,4-b]quinoxaline 3377 © Georg Thieme Verlag Stuttgart · New York Synthesis 2013, 45, 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…The NMR spectra of all peptidomimetics 6 revealed two sets of signals for most of the atoms. This indicated that compounds exist as mixtures of Z and E amide isomers (Table 1) because of restricted rotation about the C(O)-N bond at the hydrazide residue, similar to those found in pyrazinebased carboxylic acid derivatives 14 and isoindole carbohydrazides. 9,15 Previous work in our research group 9 resulted in the development of a general procedure for introducing the second amino acid residue into benzo analogues of 6 by applying the methodology of the present amino group transformation using highly reactive amino acid ester isocyanates.…”
Section: Table 1 Synthesis Ofmentioning
confidence: 59%
“…The NMR spectra of all peptidomimetics 6 revealed two sets of signals for most of the atoms. This indicated that compounds exist as mixtures of Z and E amide isomers (Table 1) because of restricted rotation about the C(O)-N bond at the hydrazide residue, similar to those found in pyrazinebased carboxylic acid derivatives 14 and isoindole carbohydrazides. 9,15 Previous work in our research group 9 resulted in the development of a general procedure for introducing the second amino acid residue into benzo analogues of 6 by applying the methodology of the present amino group transformation using highly reactive amino acid ester isocyanates.…”
Section: Table 1 Synthesis Ofmentioning
confidence: 59%